PENGARUH MOTIVASI DAN PENGAWASAN TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN LEBAK - Muhi Mukti; Aryani Hidayat (The Asia Pacific Journal Of Management Studies, 2022)
The success of an organization in achieving organizational goals is determined by the performance of its employees. The ability of employees to do the work for which they are responsible becomes a benchmark for achieving organizational goals. If an organization is able to achieve the goals that have been set, it can be said that the organization is effective. The purpose of this study (1) to determine the effect of motivation on the morale of employees at the Lebak Regency Transportation Agency. (2) to determine the effect of supervision on employee morale at the Lebak Regency Transportation Agency. (3) to determine motivation and supervision affect the morale of employees at the Lebak Regency Transportation Agency. The research method used is quantitative method using saturated sampling technique as many as 46 employees at the Department of Transportation Lebak Regency. The data collection techniques used were observation, literature study, questionnaire, and documentation. The analytical method used is the validity test, reliability test, classic assumption test, multiple linear regression analysis test, t test and F test using the SPSS V.20 program. The results of this study indicate that partially motivation has a positive and significant effect on employee morale at the Lebak Regency Transportation Agency. As well as partially supervision has a positive and significant effect on employee morale at the Lebak Regency Transportation Agency. The dominant variable that affects employee morale is motivation. The contribution of motivation and supervision variables to employee morale is 75.1% and the remaining 24.9% is contributed by other variables not examined by the author. Meanwhile, both partial and simultaneous motivation and supervision have a positive and significant effect on employee morale at the Lebak Regency Transportation Agency.